An anionic Na(i)–organic framework platform: separation of organic dyes and post-modification for highly sensitive detection of picric acid. Issue 77 (14th September 2017) - Chen, Di-Ming; Tian, Jia-Yue; Wang, Zhuo-Wei; Liu, Chun-Sen; Chen, Min; Du, Miao
Abstract : A unique nanoporous Na(i )-MOF with excellent dye separation performance is presented and the dye@MOF composite could be applied as a luminescent sensor for picric acid detection. Abstract : A cage-based anionic Na(i )–organic framework with a unique Na9 cluster-based secondary building unit and a cage-in-cage structure was constructed. The selective separation of dyes with different charges and sizes was investigated. Furthermore, the Rh6G@MOF composite could be applied as a recyclable fluorescent sensor for detecting picric acid (PA) with high sensitivity and selectivity.